Interaction effect of brain-based instructional strategy and cognitive style on students' attitude to senoir secondary school mathematics (2010)
This study investigated the interactive effect of brain-based instructional strategy and cognitive Style on students' attitude to senior secondary school mathematics. A pre-test, post-test, control group quasi-experimental design was adopted with a 2x3x2 factorial matrix. The sample was 522 senior secondary school II students from nine randomly selected schools in randomly selected schools in Oyo state, Nigeria. Five schools were randomly assigned to the experimental (Brain-BAsed Instructional STrategy- BBIS), while four schools were assinged to the control group. (Non-Brain-Based Instructional Strategy- NBBIS). The instruments were: mathematics attitude questionnaire (r=0.83), cognitive style test (r=0.81), mathematics anxiety rating scale (r=0.81). Two research questions adn one hypothesis guided the study. Data obtained from the research questions were analysed using mean scores while the hypothesis was tested at 0.05 level of significance using the analysis of covariance (ANCOVA). Brain-based instructional strategy was more effective at improving studetns' attitude to mathematics than the conventional method. Teachers of mathematics could therefore, adopt this strategy for teaching secondary school students.